(untitled) (CAHIERS MAGELLANES-NS, 2024)
The three pillars serve as the foundation for conducting risk assessments, which are incorporated into the education development plans of regions, divisions, and schools. The objectives of this study are to determine the gap between three pillars and the School Improvement Plan (SIP), to determine the significance of the relationship between the DRRM Framework Pillars and the SIP, and to improve the SIP based on the gap analysis. Similarly, implementation difficulties were also investigated. Results indicate that elementary public schools in San Mateo, Isabela are highly compliant with the Three Pillars as foundation for conducting risk assessments and hindering factors have been identified and must be addressed. The findings of this study will eventually be used to enhance the school's SIP.